Impacts of Urbanization on Extreme Regional Precipitation Events - Wei Wu; Lei Ren; Yingjian Wei; Mengjing Guo (Discrete Dynamics in Nature and Society)
Urbanization significantly impacts regional precipitation. In this study, using the city of Xi’an in China as a study area, we analyze the variation in land use and the characteristics of the variation in extreme precipitation events and discuss the response of urbanization to extreme precipitation. The main conclusions drawn are as follows. (1) The construction land area of the study area rapidly expanded in size from 80.76 km2 in 1984 to 400.3 km2 in 2018. The transfer of land use mainly occurred as the transfer from farmland to other types of land use. The urban land use intensity continues to increase. (2) The intensities and different frequency indices of extreme precipitations both show an increasing trend. In addition, the former exhibits periodic alternation with a dominant frequency of 21 years during the flood season, and both the fluctuation amplitude and maximum value of the periodic variation increase with time. (3) The urbanization in the study area has a significant impact on Rx1h and Rx2h precipitations, but little impact on the intensity of long-duration precipitation. Hence, urbanization significantly increases the intensity of extreme precipitation. After the 2000s, the urban building area, rainfall frequency, and rainfall intensity growth trends are highly consistent.